Efficacy, immunogenicity, and safety of the HPV‐16/18 AS04‐adjuvanted vaccine in Chinese women aged 18–25 years: event‐triggered analysis of a randomized controlled trial. (20th December 2016) - Zhu, Feng‐cai; Hu, Shang‐Ying; Hong, Ying; Hu, Yue‐Mei; Zhang, Xun; Zhang, Yi‐Ju; Pan, Qin‐Jing; Zhang, Wen‐Hua; Zhao, Fang‐Hui; Zhang, Cheng‐Fu; Yang, Xiaoping; Yu, Jia‐Xi; et al.
Abstract: We previously reported the results of a phase II/III, double‐blind, randomized controlled study in Chinese women (NCT00779766) showing a 94.2% (95% confidence interval: 62.7–99.9) HPV‐16/18 AS04‐adjuvanted vaccine efficacy (VE) against cervical intraepithelial neoplasia grade 1 or higher (CIN1+) and/or 6‐month (M) persistent infection (PI) with a mean follow‐up of <2 years, and immunogenicity until 7 months post‐dose 1. Here, we report efficacy and safety results from an event‐triggered analysis with 3 years longer follow‐up, and immunogenicity until M24. Healthy 18–25‐year‐old women ( N = 6051) were randomized (1:1) to receive three doses of HPV‐16/18 vaccine or Al(OH)3 (control) at M0, 1, 6. VE against HPV‐16/18‐associated CIN2+, and cross‐protective VE against infections with nonvaccine oncogenic HPV types, immunogenicity, and safety were assessed. In the according‐to‐protocol efficacy cohort, in initially seronegative/DNA‐negative women (vaccine group: N = 2524; control group: N = 2535), VE against HPV‐16/18‐associated CIN2+ was 87.3% (5.3–99.7); VE against incident infection or against 6‐month persistent infection associated with HPV‐31/33/45 was 50.1% (34.3–62.3) or 52.6% (24.5–70.9), respectively. At least, 99.6% of HPV‐16/18‐vaccines remained seropositive for anti‐HPV‐16/18 antibodies; anti‐HPV‐16 and ‐18 geometric mean titers were 1271.1 EU/mL (1135.8–1422.6) and 710.0 EU/ml (628.6–801.9), respectively. Serious adverse events were infrequent (1.7% vaccine group [ N = 3026]; 2.5% control group [ N = 3026]). Of the 1595 reported pregnancies, nine had congenital anomalies (five live infants, three elective terminations, one stillbirth) that were unlikely vaccination‐related (blinded data). VE against HPV‐16/18‐associated CIN2+ was demonstrated and evidence of cross‐protective VE against oncogenic HPV types was shown. The vaccine was immunogenic and had an acceptable safety profile. Abstract : This is the first long‐term, large‐scale, randomized clinical trial of human papillomavirus (HPV) vaccination in China, where cervical cancer is a major concern. With a mean follow‐up of approximately 57 months post‐dose 1, the HPV‐16/18 AS04‐adjuvanted vaccine was efficacious against HPV‐16/18‐associated cervical intraepithelial neoplasia and infection, immunogenic, and had a clinically acceptable safety profile in young Chinese women. Prophylactic HPV vaccination and screening could potentially reduce the high HPV epidemic and cervical cancer burden in China.